The Relationship between Interpersonal Communication of Learning Citizens and Learning Outcomes of PPKN Subjects B Package PKBM Pradana - Dian Febi Handayani; M Al Siddiq; Syuraini Syuraini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
Education which is actually a complex process and has a noble purpose will have a great impact on the perpetrators themselves. Often there are various problems that occur in dealing with the world of education, starting from the availability of facilities and infrastructure as well as the participation of the roles of various educational actors. Indeed education involves two groups consisting of teachers and students as objects to be taught. Of course, in conducting the learning process in delivering a material, not far from what we know as communication, deeper communication, and aimed at the building can be interpreted as intrapersonal communication. This communication is more binding and gives a sensitive feeling and will foster mutual respect between one group and another group. The intensity of communication that is established will result in goals that can be achieved can be achieved smoothly.Keywords: Education, Intrapersonal Communication, Learning Outcomes